2016
DOI: 10.1097/mej.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting blood sample haemolysis

Abstract: Blood sampling via an intravenous catheter was significantly associated with an increase in the likelihood of sample haemolysis compared with sampling with a needle. Wherever practicable, blood samples should be obtained via a needle in preference to an intravenous catheter. Future research should include both an economic evaluation, and staff and patient satisfaction of separating blood sampling and intravenous catheter placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Two studies (Grant, ; Ong et al, ) found that the use of a vacutainer compared with syringe resulted in higher PIVC haemolysis rates and one study (Phelan et al, ) found no differences. Three studies (Barnard et al, ; Phelan et al, ; Wollowitz et al, ) found blood drawn from the antecubital fossa were less likely to be haemolysed when compared with blood drawn from other sites, in contrast to another study (Lowe et al, ) who found no differences related to blood draw site. Two studies (Phelan et al, ; Wollowitz et al, ) found that the use of larger gauge needles were less likely to have haemolysed samples compared with a smaller gauge needle, in contrast to another study by Ong et al, who found no differences related to needle gauge size.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Two studies (Grant, ; Ong et al, ) found that the use of a vacutainer compared with syringe resulted in higher PIVC haemolysis rates and one study (Phelan et al, ) found no differences. Three studies (Barnard et al, ; Phelan et al, ; Wollowitz et al, ) found blood drawn from the antecubital fossa were less likely to be haemolysed when compared with blood drawn from other sites, in contrast to another study (Lowe et al, ) who found no differences related to blood draw site. Two studies (Phelan et al, ; Wollowitz et al, ) found that the use of larger gauge needles were less likely to have haemolysed samples compared with a smaller gauge needle, in contrast to another study by Ong et al, who found no differences related to needle gauge size.…”
Section: Resultsmentioning
confidence: 98%
“…The same study (Wollowitz et al, ) also found that the blood samples were more likely to be haemolysed if the blood collection tube was less than half full. Two studies (Phelan et al, ; Wollowitz et al, ) found if the tourniquet time was greater than 1 min blood samples were more likely to be haemolysed with one study (Barnard et al, ) finding no differences. Two studies (Barnard et al, ; Wollowitz et al, ) found blood samples were more likely to be haemolysed if the venepuncture was difficult (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were published by Blazys (1999) and Becan-McBride (1999). A study by Barnard et al (2016) found that the device type used to obtain a sample was a significant factor in the haemolysis rate, with sampling via an intravenous catheter associated with a significant increase in likelihood compared to sampling with a needle.…”
Section: Venepuncture Procedures Analysismentioning
confidence: 99%
“…The literature review identified that another key variable that might influence procedure outcomes was the device type used to obtain the sample, e.g. Jagger et al (1988) and Barnard et al (2016). The questionnaire included a question on the types of needle used and associated estimated probability of successful blood sample collection and needle stick injury risk.…”
Section: Venepuncture Procedures Analysismentioning
confidence: 99%